2015
DOI: 10.1016/j.foodres.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling, antioxidant and antibacterial activities of Brazilian propolis: Use of correlation and multivariate analyses to identify potential bioactive compounds

Abstract: The production of propolis by honeybees results from a selective collection of exudates from various plant species and present many potentialities in the pharmaceutical industry. The objective of this study was to investigate the chemical profile of Brazilian propolis, as well as their in vitro antioxidant and antibacterial activities. Gas chromatography-mass spectrometry was applied for chemical profiling of propolis extracts. Total phenolic compounds were quantified by Folin-Ciocalteu and antioxidant propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
4
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 49 publications
3
78
4
9
Order By: Relevance
“…Antioxidant potency is usually associated with the content of phenolic compounds due to their extensive conjugated π-electron systems that facilitate the donation of electrons from the hydroxyl moieties to oxidizingradical species. 22 From the calculation data, it is known that PEE from this research are strong antioxidant, according to Jun et al (2003), 25 that classification of antioxidant power are strong antioxidant with strength level (IC 50 <50 ppm), active (IC 50 50-100 ppm), moderate (IC 50 101-250 ppm), weak (IC 50 250-500 ppm), and inactive (IC 50 > 500 ppm). 25 The EC 50 DPPH radical scavenging activity of Propolis in this research are inferior to Bolivian Propolis those reported by Nélida Nina (2016) 17 22 ranged from 21.50 to 78.77 μg/mL.…”
Section: Discussionmentioning
confidence: 79%
“…Antioxidant potency is usually associated with the content of phenolic compounds due to their extensive conjugated π-electron systems that facilitate the donation of electrons from the hydroxyl moieties to oxidizingradical species. 22 From the calculation data, it is known that PEE from this research are strong antioxidant, according to Jun et al (2003), 25 that classification of antioxidant power are strong antioxidant with strength level (IC 50 <50 ppm), active (IC 50 50-100 ppm), moderate (IC 50 101-250 ppm), weak (IC 50 250-500 ppm), and inactive (IC 50 > 500 ppm). 25 The EC 50 DPPH radical scavenging activity of Propolis in this research are inferior to Bolivian Propolis those reported by Nélida Nina (2016) 17 22 ranged from 21.50 to 78.77 μg/mL.…”
Section: Discussionmentioning
confidence: 79%
“…) (Table S2). Based on these results we can conclude that the mechanisms underlying the antimicrobial as well as the antioxidant activities involved composite features reflected by synergistic or antagonistic effects among the metabolites existing within the extracted oils or extracts (Sasidharan et al ., ; Bittencourt et al ., ; Pérez et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be stressed that red propolis has been suggested to be the only propolis type derived from a plant from the Leguminosae family (D. ecastaphyllum), rich in isoflavones such as genistein and formononetin. Although flavonoids exhibit pleiotropic activity affecting several different targets, and synergistic effects cannot be ruled out, our results suggest that the isoflavone formononetin is responsible at least partially for the antimicrobial activity of red propolis 20 Bittencourt et al [30] Twenty-nine metabolites were identified along with 34 other metabolites that were classified into the following classes: triterpenoids (12), acetyltriterpenoids (3), sesquiterpenes (6), steroids (4), and hydrocarbons (9). The antioxidant capacity (IC50) ranged from 21.50 to 78.77 μg/mL, whereas the content of total phenolic compounds ranged from 31.88 to 204.30 mg GAE/g of dry weight.…”
Section: N°bibliographic Referencementioning
confidence: 77%